The stability of pexider type functional equation in intuitionistic fuzzy banach spaces via fixed point techique - P. Mondal; N. Chandra Kayal; T. K. Samanta (Journal of Hyperstructures, 2015)
The object of the present paper is to appraise generalization of the Hyers-Ulam-Rassias stability theorem for Pexider type functional equation f ( 2 x + y ) − f ( x + 2 y ) = 3 g ( x ) − 3 h ( y ) ( 1 ) in intuitionistic fuzzy Banach spaces and stability results have been obtained by a fixed point method . This method shows that the stability is related to some fixed point of a suitable operator .